2011
DOI: 10.1038/onc.2011.364
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LIN9, a member of the DREAM complex, cooperates with SV40 large T antigen to induce genomic instability and anchorage-independent growth

Abstract: The DREAM complex is an important regulator of mitotic gene expression during the cell cycle. Here we report that inactivation of LIN9, a subunit of DREAM, results in premature senescence, which can be overcome by the SV40 large T (LT) antigen. Together with the observation that p16 INK4a and p21 Waf1 are upregulated upon loss of LIN9, these results indicate that senescence is triggered by the pRB and p53 tumor suppressor pathways. We also find that LIN9-null cells that escape senescence are chromosomally inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The RB pocket protein-E2F pathway is a target for several oncoproteins originating from DNA viruses with HPV E7, adenovirus early-region 1A (E1A) and polyomavirus large T-antigens as prominent examples (29,99). Consistent with this notion, also SV40 large T was recently reported to impair DREAM function (100,101). …”
Section: Discussionsupporting
confidence: 71%
“…The RB pocket protein-E2F pathway is a target for several oncoproteins originating from DNA viruses with HPV E7, adenovirus early-region 1A (E1A) and polyomavirus large T-antigens as prominent examples (29,99). Consistent with this notion, also SV40 large T was recently reported to impair DREAM function (100,101). …”
Section: Discussionsupporting
confidence: 71%
“…Several other viral oncoproteins target the pocket proteins through LxCxE motifs, including adenovirus early-region 1A (E1A) and large T antigens of several polyomaviruses, such as SV40, JCV and BKV 58 . Consistent with this notion, also SV40 large T was reported to impair DREAM function 59, 60 .…”
Section: Discussionsupporting
confidence: 61%
“…Expression of genes encoding these proteins as well as eight additional mitotic kinesins (36) were downregulated following BETi treatment. Prior studies have shown that loss of LIN9 expression produces polyploid cells with aberrant nuclei and induces senescence (49, 55). Thus, data presented herein not only confirm the impact of LIN9 on mitosis, but also implicate LIN9 as an intermediate between BET proteins and effective mitosis in TNBC.…”
Section: Discussionmentioning
confidence: 99%